Asimilasi Golongan Etnis Arab di Kelurahan Kademangan Kulon Bondowoso: Assimilation of the Arab Ethnic Group in Kademangan Kulon Subdistrict, Bondowoso - H. Sahilun A. Nasir (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2002)
The assimilation of foreign-descent groups in Indonesia is a critical phenomenon, particularly given the nation’s pluralistic social fabric. While much attention has been given to the ethnic Chinese, the Arab minority remains underexplored despite their distinct historical trajectory and integration patterns. This study addresses this gap by examining the process, extent, and limitations of assimilation among the Arab community in Kademangan Kulon, Bondowoso, a settlement where they constitute the majority. Drawing on acculturation and biculturalism theories, this qualitative study utilised document analysis, observation, and in-depth interviews with local officials, religious leaders, youth, and residents. The findings reveal significant assimilation across several domains: intermarriage with indigenous populations, daily language use (Arabic, Madurese, Indonesian), shared religious arts (samroh, gambus), economic participation, and educational integration. Importantly, Islamic faith emerges as the primary driver of this assimilation, fostering common values and social cohesion. However, assimilation remains incomplete due to persistent internal social stratification, particularly the rigid distinction between Sayid and non-Sayid groups and the associated concept of kafa’ah in marriage. The study concludes that while Islam effectively bridges ethnic divides, genealogical hierarchies hinder full integration. Recommendations include further research on the role of religious leadership in mitigating these stratifications and policy attention to inclusive community development. Asimilasi golongan keturunan asing di Indonesia merupakan fenomena krusial dalam dinamika masyarakat majemuk. Kelompok etnis Arab, meskipun kurang mendapat perhatian dibandingkan etnis Tionghoa, memiliki pola asimilasi yang khas dan penting untuk dikaji. Penelitian ini bertujuan menganalisis proses, capaian, dan hambatan asimilasi etnis Arab di Kelurahan Kademangan Kulon, Bondowoso, di mana mereka menjadi populasi mayoritas. Dengan menggunakan teori akulturasi dan budaya rangkap, penelitian kualitatif ini mengumpulkan data melalui dokumentasi, observasi, dan wawancara mendalam dengan perangkat kelurahan, tokoh agama, remaja, dan warga setempat. Hasil penelitian menunjukkan asimilasi telah berlangsung dalam berbagai aspek seperti perkawinan dengan penduduk pribumi, penggunaan bahasa (Arab, Madura, Indonesia), kesenian bernuansa Islam (samroh, gambus), kegiatan ekonomi perdagangan, serta partisipasi dalam lembaga pendidikan campuran. Faktor pemersatu utama adalah kesamaan agama Islam. Namun, asimilasi belum tuntas karena masih adanya stratifikasi sosial internal, terutama pembedaan antara golongan Sayid dan non-Sayid serta penerapan konsep kafa’ah dalam pernikahan yang menghambat perkawinan lintas golongan. Kesimpulannya, agama Islam berperan sebagai perekat asimilasi, tetapi hierarki genealogi budaya masih menjadi penghalang. Rekomendasi penelitian ini adalah perlunya kajian lebih lanjut tentang peran kepemimpinan agama dalam menjembatani stratifikasi tersebut.